2020
DOI: 10.1080/15583058.2020.1751343
|View full text |Cite
|
Sign up to set email alerts
|

Vernacular Caramel´s Adobe Masonry Dwellings – Material Characterization

Abstract: In Pinhal Novo, Palmela, and neighboring municipalities, southern Lisbon region, there are a great number of small adobe masonry dwellings, made in the first half of the 20 th century. The vernacular dwellings were constructed by families that came from the north/center region of Portugal to work at the local manors, and were called Caramel´s. Adobe samples from three of these dwellings were collected in Pinhal Novo and Moita, and tested for particle size distribution, X-ray diffraction, color, bulk density, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Because high content of fine granular argillaceous cement would make the adobe unstable in the presence of water, resulting in the cracking of the adobe masonry, weakening or even destroying the stability of the building structure, it was necessary to add a certain amount of fiber or coarse sand to improve the properties of adobe (Dormohamadi & Rahimnia, 2020; Mellaikhafi et al, 2021; Quagliarini & Lenci, 2010). Interestingly, the adobe remains found in different civilizations around the world displayed that the ancient humans often used soil containing a large amount of argillaceous cement to make adobe (Costi de Castrillo et al, 2017; Mauricio et al, 2021; Silva et al, 2020). They would like select fibers to improve the performance of adobe but rarely added coarse aggregate to it (Houben et al, 2004; Li, 2016; Mortada, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Because high content of fine granular argillaceous cement would make the adobe unstable in the presence of water, resulting in the cracking of the adobe masonry, weakening or even destroying the stability of the building structure, it was necessary to add a certain amount of fiber or coarse sand to improve the properties of adobe (Dormohamadi & Rahimnia, 2020; Mellaikhafi et al, 2021; Quagliarini & Lenci, 2010). Interestingly, the adobe remains found in different civilizations around the world displayed that the ancient humans often used soil containing a large amount of argillaceous cement to make adobe (Costi de Castrillo et al, 2017; Mauricio et al, 2021; Silva et al, 2020). They would like select fibers to improve the performance of adobe but rarely added coarse aggregate to it (Houben et al, 2004; Li, 2016; Mortada, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding another regions in Portugal, Fonseca (2007) identified adobe with 0.40 m × 0.20 m × 0.12 m (length × width × thickness) in Avis, Alentejo, (Figure 1A), identified adobe with 0.51-0.50 m x 0.38-0.30 m x 0.10 m in Setúbal region, (Figure 1A), and Varum et al (2008) and several other researchers identified adobe with 0.45 m × 0.30 m × 0.15 m in the district of Aveiro (Figure 1A). Contrary to what happens in other regions, such as Pinhal Novo, Setúbal district (Sampaio et al, 2017;Silva et al, 2020) where the adobe width defined the walls thickness, in Leiria that was defined by the adobe length in the structural exterior walls. However, the wall thicknesses were not so different between both regions as Leiria's adobe length (Table 1) seems to be close to Setúbal's adobe width .…”
Section: Surveymentioning
confidence: 89%
“…However, the characterization of materials is still scarce. Some studies have already been performed on vernacular dwellings, namely lime-stabilized adobe masonry from Aveiro region (Coroado et al, 2010;Silveira et al, 2012;Costa et al, 2019), unstabilized adobe masonry from Setúbal region (Silva et al, 2020) and rammed earth from Alentejo (Gomes et al, 2014;Gomes et al, 2019) or from Western Algarve (Mateus et al, 2015;Mateus et al, 2019).…”
Section: Earth Construction In Portugalmentioning
confidence: 99%
See 2 more Smart Citations